The macroeconomic factors that contribute to the non-performing loan in Malaysia / Syazwani Kamal - Kamal, Syazwani (Faculty of Business and Management, 2017)
The aim of this study is to investigate the macroeconomic factors that contribute to the non-performing loan in Malaysia. The variables used to examine the relationship with the non-performing loan (NPL) are interest rate(INT), exchange rate(EXC) and inflation rate(INF). The data were collected from databases derived from Bank Negara Malaysia and Department of Statictics Malaysia on quarterly basis from 2005 to 2015. In the process of findings there are few types of analysis were tested using E-views Version 9.5, such as unit root test, descriptive analysis, correlation analysis, single linear regression,multiple linear regression and more. The results indicate that exchange rate is the only significant factor that determine the non-performing loan in Malaysia. However, this result was not sufficient to be used since there are few diagnostic problems such as autocorrelation problem, heteroskedasticity problem and others. For future research, it is suggested that the researcher should think an advanced method to clean up all the problem, get the easier data and others.